Assessment of Wastewater Quality Discharged from Some Selected Bakeries in Benin City, Nigeria (Journal of Engineering, 2025)
Nigeria's limited freshwater resources are at risk due to the discharge of wastewater from water-intensive industries, such as food processing, that does not comply with the regulations of the National Environmental Standards and Regulation Enforcement Agency (NESREA). This could significantly harm both the ecosystem and human health. This study aims to assess the physicochemical and biological properties of wastewater discharged from selected bakeries in Benin City, Nigeria, to determine compliance with NESREA standards and highlight potential environmental risks. Wastewater samples were randomly collected from five bakeries in Benin City and examined for their physicochemical and biological features. The findings indicated that, except for potential of Hydrogen (pH), total dissolved solids (TDS), chemical oxygen demand (COD), chloride (Cl⁻), Ammonium Nitrogen (NH₄N), and lead (Pb), all other parameters were within NESREA's permitted limits for food industry effluent discharge. The average pH value (5.9) was below the permitted range, but the average TDS (4754.2 mg/l), COD (1058.34 mg/l), NH₄N (3.068 mg/l), Cl (2984.86 mg/l), along with Pb (0.0724 mg/l) values are substantially over NESREA standards. These results show non-compliance with NESREA rules, stressing the necessity for regulatory entities to monitor the quality of bakery wastewater in the research region to guarantee high-quality effluent discharge.